A local risk map using field observations of the Asian longhorned beetle to optimize monitoring activities. (17th January 2018) - Fragnière, Y.; Forster, B.; Hölling, D.; Wermelinger, B.; Bacher, S.
Abstract: The Asian longhorned beetle Anoplophora glabripennis (Motschulsky) (Coleoptera: Cerambycidae) is one of the most dangerous xylophagous pests affecting broadleaf trees in the world. Eradication programmes are undertaken in non‐native regions, requiring extensive resources and involving high costs. An adapted strategy must be set up to optimize the ratio cost/probability of success. We developed a method to generate a risk index of A. glabripennis presence at a local scale, in the surrounding area of an infestation, using field observations (counts of adult insects, exit holes and infested trees). The method, mathematically based on the bivariate symmetric Laplace distribution, has thus reasonable input requirements. The output risk map is easy to interpret and can be directly used by decision‐makers. We used our approach in three infestations in Switzerland. The risk map represented well the insect pressure (beetle population density). We highlighted the fact that survey boundaries, commonly chosen using constant distances from the infestation, should be selected regarding the spatial distribution of the insect pressure, to prioritize monitoring activities. The risk map provides a helpful instrument for advanced survey planning after a first overview, for example to decide which area and which host trees should be inspected for infestations.